Posterior spinal fusion in surgery of the cervical spine - Barysh, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article contains results of surgical treatment of 15 patients with injuries and diseases of their cervical spine with different localization, where a new technique of posterior spinal fusion and a fixing device on the basis of rods were used. An analysis of these results with help of the criteria, developed by the author, for an integrated assessment of the performed surgical interventions makes it possible to state that it is effective and safe to employ the above technique for posterior spinal fusion with different length and localization, as well as in cases of bone element defects of the posterior support complex of the cervical vertebral motor segments.